THE RELATIONSHIP BETWEEN AGE AND BMI OF PREGNANT WOMEN AND THE INCIDENCE OF PREECLAMPSIA - Siti Asiyah; Sri Handayani; Luluk Khusnul Dwihesti (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2026)
Preeclampsia is a hypertensive disorder during pregnancy that is a significant cause of maternal and neonatal morbidity and mortality. This condition is characterized by the appearance of high blood pressure after ≥20 weeks of gestation accompanied by proteinuria or other organ dysfunction, and often leads to serious complications if not detected early. Preeclampsia is also closely related to maternal conditions such as obesity, extremes of age, and other metabolic factors. These factors are important to understand because they provide direction for early prevention efforts and effective risk control. The purpose of this study was to determine the relationship between maternal age and BMI with the incidence of preeclampsia in Boyolali in 2026. This study uses quantitative research with an analytical observational study design with a cross-control approach.. The study population was all pregnant women in the working area of Klego I, II, and Karanggede Health Centers. Sampling in this study used total sampling, namely 202 respondents. The research instrument was a summary sheet. The results of this study found a relationship between maternal age with the incidence of preeclampsia (p value = 0.001) and BMI (p value = 0.000) The age variable has a probability of approximately 2.3 times greater of experiencing preeclampsia compared to BMI.s The conclusion is that there is a significant relationship between age and BMI with the occurrence of preeclampsia.